Elements of functional training in volleyball training sessions for young women aged 16-17 - Obvintsev, A.; Grets, I.; Bulkova, T. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to experimentally prove the effectiveness of volleyball training sessions with elements of functional training for young women aged 16-17.